Penerapan Manajemen Mutu Pelayanan Rumah Sakit Oleh Tenaga Kesehatan di RS. Mitra Medika Premiere Medan - Arifah Devi Fitriani; Deli Theo; Meriahta Sitepu; Teguh Suharto; Mhd. Aulia Rahman4; Sari Safitri5 (Lembaga Pengembangan Kinerja Dosen, 2025)
Hospital service quality management is a crucial aspect of the healthcare service system, aimed at ensuring that every patient receives safe, effective, and high-quality care. In the era of global competition and rising patient expectations, hospitals are required not only to provide adequate healthcare services but also to continuously and sustainably improve the quality of their services. Good quality management assists hospitals in identifying, measuring, and improving areas that require enhancement, as well as ensuring compliance with service standards set by accreditation bodies and regulators. With effective quality management, hospitals can reduce medical risks, enhance patient satisfaction, and ultimately strengthen the institution's reputation. This approach also plays a vital role in optimizing resource utilization and improving operational efficiency, which ultimately contributes